Terminal Care Education in Medical School Curriculums: A Comparison Between Japan and Other Countries - SHOJI, Shinichi (Igaku Kyoiku / Medical Education (Japan), 1995)
To investigate the present state of teaching on terminal care and death in medical school pregraduate curriculums, I conducted a survey of 80 Japanese medical schools using a questionnaire in May and June, 1993. Ninety-one percent of the schools responted. Of the 73 responding schools, 24 stated that they have no formal educational program for medical students concerning the death and terminal care. Forty-nine schools (67%) said that they have terminal care and death education courses in their curriculum at present. This rate is the same as that about 20 years ago in the United States. In Japan, most schools have only lectures on the subject matter, of variable total duration, ranging from 1 to 32 hours (mean 6.4 hours). Only 5 schools have practical training with a chance for medical students to meet terminal patients. Practical training is conducted in hospice or hospice wards in 3 schools, in a pain clinic in 1 school, and in a standard inpatient ward in 1 school. Seven schools have training courses without participation by terminal patients, using role-playing (4 schools), and expression of student's opinions (3) instead. In England, the United States, and Australia, practical training with frequent one-on-one meetings between medical students and terminal patients (as patient-tutors) was reported.